FORTIFIKASI EKSTRAK LIMBAH KULIT BUAH MELINJO (Gnetum gnemon) PADA PAKAN TERHADAP WARNA IKAN MAS KOKI (Carassius auratus) - Ardiansyah Kurniawan; Achmad Basorudin; Eva Prasetiyono (Universitas Muhammadiyah Gresik, 2022)
Color is one of the parameters in determining the value of ornamental fish. Goldfish (Carassius auratus) as one of the popular ornamental fish in Indonesia also requires the best color for its quality. One of the factors that affect the brightness of fish color is pigment-forming materials that can be obtained from feed. Melinjo fruit peel (Gnetum gnemon), which is often a waste, has the potential to be an ingredient to maintain the brightness of fish color with its carotenoid content. Research on the fortification of Melinjo fruit peel extract on goldfish feed used a completely randomized design (CRD) with 4 treatments, namely (A) untreated feed, (B) feed with the addition of 3.5 ml/100 g of feed extract, (C) 4 ml /100 g feed, and (D) 4.5 ml/100 g feed. The average increase in fish color RGB at the location under the dorsal fin with treatment for 40 days was (A) 5.13, (B) 6.4, (C) 11.1 and (D) 12.77. The four treatments showed significantly different results with the best results being 4 ml and 4.5 ml per 100 grams of feed. Melinjo fruit peel which is an organic waste can be used to increase the color brightness of ornamental fish through the addition of its extract in feed.